2022
DOI: 10.5194/acp-22-12311-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Plume heights of the April 2021 La Soufrière eruptions from GOES-17 side views and GOES-16–MODIS stereo views

Abstract: Abstract. We estimated geometric plume heights for the daytime eruptions of La Soufrière in April 2021 using visible red band geostationary side views and geostationary–polar orbiter stereo views. Most of the plumes either spread near the tropopause at 16–17 km altitude or penetrated the stratosphere at 18–20 km altitude. Overshooting tops reached heights of up to 23 km. These geometric heights were compared with radiometric heights corresponding to the coldest plume temperature, which usually represent ambigu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…La Soufrière, on the island of Saint Vincent, began explosively erupting on the morning of 9 April 2021 after months of expansion of its lava dome (Figure 2d). Dozens of distinct eruptions were identified between the initial eruption and 22 April (Babu et al., 2022; Horváth et al., 2022). The most violent eruptions occurred on 11 April, with the largest beginning around 1330 UTC.…”
Section: Methodsmentioning
confidence: 99%
“…La Soufrière, on the island of Saint Vincent, began explosively erupting on the morning of 9 April 2021 after months of expansion of its lava dome (Figure 2d). Dozens of distinct eruptions were identified between the initial eruption and 22 April (Babu et al., 2022; Horváth et al., 2022). The most violent eruptions occurred on 11 April, with the largest beginning around 1330 UTC.…”
Section: Methodsmentioning
confidence: 99%
“…The La Soufrière eruption started on 09 April at 12.41 UTC (Joseph et al., 2022) and was characterized by 43 individual phases in the first 4 days and 49 phases during the entire eruption period from 09 to 22 April (Horváth et al., 2022). The detected eruption phases lasted between 10 min and 1 hr, and they reached plume heights between 5.7 and 18.3 km above the vent.…”
Section: Model and Data Descriptionmentioning
confidence: 99%
“…As input parameters, FPlume needs estimates of the plume height, the exit temperature, exit velocity, and exit volatile fraction. The plume heights were geometrically derived from GOES‐17 (Geostationary Operational Environmental Satellite‐17) near‐limb imagery at daytime and are temperature‐derived from GOES‐16 at nighttime (Horváth et al., 2022). A detailed description of the geometric side view technique is given in Horváth et al.…”
Section: Model and Data Descriptionmentioning
confidence: 99%
“…On April 9 th , 2021, La Soufrière (13.3˚N, 61.2˚W) began erupting explosively (maximum volcanic explosivity index of four). Horváth et al (2022) identified 49 distinct eruptive events between April 9-22 nd . The stratospherically relevant eruptive events occurred primarily between April 9-12 th (Taylor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Peak SO2 column loading was measured to be between 0.3-0.4 Tg (Bruckert et al, 2023;Taylor et al, 2022). The bulk of the plumes and SO2 spread near the tropopause (~17-18 km) with overshooting tops reaching up to 23 km (Horváth et al, 2022;Taylor et al, 2022). Multi-angle Imaging SpectroRadiometer (MISR) observations also indicate that the volcanic ash plume reached levels above 20 km (NASA Earth Applied Sciences Disasters Program).…”
Section: Introductionmentioning
confidence: 99%